2021
DOI: 10.1111/jocn.15599
|View full text |Cite
|
Sign up to set email alerts
|

Team‐based learning in nursing education: A scoping review

Abstract: Aims and objectives To explore the use and student outcomes of Team‐Based Learning in nursing education. Background Team‐Based Learning is a highly structured, evidence‐based, student‐centred learning strategy that enhances student engagement and facilitates deep learning in a variety of disciplines including nursing. However, the breadth of Team‐Based Learning application in nursing education and relevant outcomes are not currently well understood. Design A scoping review of international, peer‐reviewed resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
(357 reference statements)
2
23
0
1
Order By: Relevance
“…TBL could significantly improve students' academic knowledge, clinical performance, competency skills, satisfaction, perceptions, and attitudes. The first significant advantage of this review was that we only enrolled RCT design trials because previous reviews of studies of TBL report on the relative lack of randomized controlled studies ( 9 , 15 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBL could significantly improve students' academic knowledge, clinical performance, competency skills, satisfaction, perceptions, and attitudes. The first significant advantage of this review was that we only enrolled RCT design trials because previous reviews of studies of TBL report on the relative lack of randomized controlled studies ( 9 , 15 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a growing number of studies regarding the effectiveness of TBL in health professions {i.e., pharmacy ( 7 ), medicine ( 8 ), midwifery ( 9 ), and nursing education ( 10 14 ). A scoping review showed that TBL had been applied in nursing education over the last decade and reported outcomes involving students' knowledge/academic performance, student experience, satisfaction, or perceptions of TBL, student engagement, behaviors/attitudes toward TBL, and teamwork, team performance/collective efficacy ( 15 ). The significant gaps identified in this scoping review were the lack of RCTs, with only 3 out of 41 included studies being RCTs [dominant study designs were evaluation of TBL in isolation ( n = 19)].…”
Section: Introductionmentioning
confidence: 99%
“…Being together for a long period gave them an emotional dependence to comfort and encourage each other. Another finding of this study was that the participants, together with their peers, constituted a cordial, reciprocal, and harmonious academic environment, where they became more confident in their capacity to overcome academic challenges [ 30 , 31 ]. Nursing students from other grades also affirmed the importance of peer involvement in collaborating to reach goals as well as the importance of the learning environment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the effectiveness of TBL, showing its superiority over conventional face-to-face lecturing while also involving communication skills and abilities, critical thinking, and problem-solving skills [ 16 , 20 ]. Aside from being applied to students, TBL has also been applied to educational training for clinical nurses [ 21 ]. Studies revealed that clinical nurses perceived increased learning quality and positive learning experiences with this learning method [ 22 ] and acquired knowledge and skills [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%